How to measure protectionism in international trade in XXI century? The regional barometer of protectionism – case of Poland - Piekutowska, Agnieszka; Konopka, Paweł (Technological and Economic Development of Economy, 2023)
The purpose of the paper is to present a methodology for measuring contemporary protectionism – based on data from Poland. In light of the difficulties in assessing all trade barriers, an approximation was proposed: the regional barometer of protectionism (RBP). Recognizing that 21st century protectionism is observable only to a certain extent, the research is based on data that reflect the level of this phenomenon – i.e., media releases as well as Global Trade Alert data. In constructing this barometer, the TOPSIS method (a Technique for Order Preference by Similarity to an Ideal Solution) was used. The RBP constructed (for 2009–2020) is the first regional barometer of protectionism. The results of the research reveal the level and dynamics of protectionism in the case of Poland. This RBP improves the methodology of foreign trade analysis by providing a thorough basis for further research into both the effects and causes of protectionism; this paper presents initial explanations for the latter. Furthermore, after the barometer of protectionism is constructed, trade barriers may eventually be included in further research for models designed to explain Polish trade.